Pengembangan Modul Bernuansa Pendidikan Karakter yang Dilengkapi Mind Map pada Materi Sistem Peredaran Darah untuk SMA - Rahmi, Miftahur Rahmi; Lufri, Lufri; Ilyas, Zulyusri (Jurnal Bioconcetta, 2017)
The aim of this research is to test the validity and practicality biology course module nuanced character education with mind map in circulation system topic for a 2nd grade developed to Senior High School. This research is a development research use four D models that is define phase, design phase, develop phase and disseminate phase. Stage implemented until the develop phase is validity test and practicality test. For validity tested by 6 validators, and for the practicaality tested by 3 teachers and 20 students of SMAN 4 Padang. Data were obtained from questionnaire validation and questionnaire practicality. The results showed that the module developed is very valid (89.72%) and practical by the teacher with the value is 84, 81% and 88,64% by the students